The Politics of Knowledge - Swee-Hock, Saw (Book collections on Project MUSE., 2008)
The publication of this book, comprising chapters written by distinguished scholars, is a timely recognition that these days we are bombarded by suggestions that knowledge is power, that we are operating in a knowledge economy, and that the greatest driver for financial growth and national development is the knowledge industry. There are more sources of knowledge available to a wider range of the world's population than ever before. The Internet has made the dissemination of knowledge possibl ...